Resveratrol on the Metabolic Reprogramming in Liver: Implications for Advanced Atherosclerosis - Ma, Ying; Li, Dongliang; Liu, Wenfeng; Liu, Xiaoxiao; Xu, Yingqi; Zhong, Xinrui; Zhi, Fengnan; Jia, Xueling; Jiang, Yanan; Fan, Yuhua (Frontiers in Pharmacology, 2021)
Background/Aims: Atherosclerosis (AS) is one of the major leading causes of death globally, which is highly correlated with metabolic abnormalities. Resveratrol (REV) exerts beneficial effect on atherosclerosis. Our aim is to clarify the involvement of liver metabolic reprograming and the atheroprotective effects of REV. Methods: ApoE-deficient mice were administered with normal diet (N), high fat diet (H), or HFD with REV (HR). Twenty-four weeks after treatment, Oil Red O staining was used to assess the severity of AS. Non-targeted metabolomics was employed to obtain metabolic signatures of liver from different groups. Results: High fat diet induced AS was alleviated by REV, presents as less lipid accumulation in the lesions. The metabolic profiles of liver tissues from N, H and HR groups were analyzed. A total of 1146 and 765 differentially expressed features were identified between N and H groups, and H and HR groups, respectively. KEGG enrichment analysis uncovered several metabolism related pathways, which are potential pathogenesis mechanism and therapeutic targets including “Primary bile acid biosynthesis”, “Phenylalanine metabolism”, “Glycerophospholipid metabolism”, etc. We further conducted trend analysis using 555 metabolites with one-way ANOVA P<0.05 and PLS-DA VIP>1. We found that REV could reverse the detrimental effect of high fat diet induced atherosclerosis. These metabolites were enriched in pathways including “Biosynthesis of unsaturated fatty acids”, “Intestinal immune network for IgA production”, etc. The metabolites-involved in these pathway maybe potential biomarkers for AS-related liver metabolic reprogramming and the mechanism of REV treatment. Conclusions: REV exerted atheroprotective effect partially by modulating liver metabolism.